O problema do método no campo da ciência e religião: uma avaliação crítica à abordagem metodológica de Nancey Murphy - Cravelin, José Felipe (2022)
This dissertation is a critical assessment of the field of science and religion through the philosopher Nancey Murphy's proposal to understand theological activity as scientific in her book Theology in the Age of Scientific Reasoning (1990). Murphy intends to use the methodological success of the natural sciences in theological activity to sustain that theology shares common standards of rationality with science. She makes use of the philosopher Imre Lakatos’s research programs aiming to apply it in theologies. To critically evaluate Murphy's proposal, we intend to establish a reconstruction of the central notions featured in her book, address some difficulties of this philosophical project, and, finally, propose a possible alternative path. Such aims are presented over four chapters. In the first, a reconstruction of the initial problem of Murphy's work is made, that is, the decline in credibility of Western theistic theologies occasioned by important epistemological changes in the modern period. Such changes formed the background for philosopher David Hume's criticisms of theistic theologies, promoting a deep crisis. Thereof, the challenge taken by Murphy was one of providing a way out of this crisis. In the second chapter, a reconstruction of the main scientific methodologies developed in the philosophy of science in the 20th century is established: logical positivism, falsificationism, the theory of paradigms and the methodology of research programs. Subsequently, Murphy's reasons for choosing research programs as a way to resolve the crisis of theistic theologies are discussed. In the third chapter, Murphy's application of research programs to two theologies, Catholic Modernism and the theology of Wolfhart Pannenberg, is presented. In the second part of the chapter, a critique of Murphy's methodological project is offered. At the end of the chapter, it is indicated how Murphy's relationship with the field of science and religion takes place. It seeks to point out that this field has as its main characteristic the attempt to find methodological parity between scientific and theological activity. However, such a strategy encounters objections from the anti-essentialist position. In the fourth chapter, such an anti-essentialist position is presented from the viewpoint of Josh Reeves (2019) and Peter Harrison (2015). It is intended to point out, through anti-essentialism, that the problem of authors like Murphy is to adopt methodologies that presuppose the existence of certain essential characteristics in the concepts of science, religion and theology, although contested by historical study. Indeed, by revealing a divergence between history (descriptive) and philosophy (normative), Reeves proposes a descriptivist solution for the field of science and religion. However, certain arguments are offered to support that the theory of traditions of the philosopher Alasdair MacIntyre (2001;1991) is preferable over the descriptivist proposal of Reeves.